Using a CO2 Surgical Laser for Piglet Castration to Reduce Pain and Inflammation, and to Improve Wound Healing - A. V. Viscardi; C. A. Cull; M. D. Kleinhenz; S. Montgomery; A. Curtis; K. Lechtenberg; J. F. Coetzee (Kansas Agricultural Experiment Station Research Reports, 2020)
The objectives of this preliminary study were to determine the ability of a CO2surgical laser to 1) reduce pain, 2) reduce inflammation, and 3) improve wound healing of piglets undergoing surgical castration. Two-day old male Yorkshire × Landrace piglets were used and randomly assigned to one of three treatments (n= 10 piglets/treatment group): surgical castration with the CO2laser, surgical castration with a scalpel, or sham (uncastrated control). Piglets were video recorded in their pens for 1 h pre-procedure and from 0-2, 6-8, and at 24 h post-procedure for behavior scoring. Surgical site images were collected at baseline, 0, 8, 24, 48, 72, 96, 120, 144, and 168 h post-castration for wound healing assessment. Infrared thermography (IRT) images of the surgical site were also taken at baseline, 0, 0.5, 8, and 24 h post-procedure to assess inflammation. Finally, blood was collected from each piglet at baseline and 0.5 h post-castration to assess cortisol levels, prostaglandin E metabolite (PGEM), and pig-major acute phase protein (pig-MAP) concentration. Laser-castrated piglets displayed more pain behaviors across the observation period than scalpel-castrated piglets (P= 0.049). Laser-castrated piglets also displayed significantly more agonistic behavior than both scalpel-castrated and sham piglets (P= 0.005 andP= 0.036, respectively); yet, laser-castrated piglets had significantly lower temperatures at the site of incision compared to scalpel-castrated piglets (P= 0.0211). There was no significant difference in wound healing or any of the blood parameters assessed between laser-castrated and scalpel-castrated piglets. There was evidence of thermal tissue damage on the scrotum of piglets that were castrated using the CO2laser. This may have resulted in the unremarkable healing time and the increased pain behavior observed in this study. The surgical laser technique should be refined before conclusions can be made regarding the utility of a CO2laser for piglet castration.
Keywords: animal welfare; castration; CO2 surgical laser; piglet; pain; refinement